Hemoptysis caused by Parvimonas micra: case report and literature review - Shao, Axue; He, Qingqing; Jiao, Xin; Liu, Jianbo (Frontiers in Public Health, 2024)
Background: Parvimonas micra (P. micra), a Gram-positive anaerobic bacterium, exhibits colonization tendencies on oral mucosal and skin surfaces, potentially evolving into a pathogenic entity associated with diverse diseases. The diagnostic trajectory for P. micra-related diseases encounters delays, often with severe consequences, including fatality, attributed to the absence of symptom specificity and challenges in culture. The absence of a consensus on the diagnostic and therapeutic approaches to P. micra exacerbates the complexity of addressing associated conditions. This study aims to elucidate and scrutinize the clinical manifestations linked to P. micra, drawing insights from an extensive literature review of pertinent case reports.Case Presentation: A 53-year-old male sought medical attention at our institution presenting with recurrent hemoptysis. Empirical treatment was initiated while awaiting pathogen culture results; however, the patient's symptoms persisted. Subsequent metagenomic next-generation sequencing (mNGS) analysis revealed a pulmonary infection attributable to P. micra. Resolution of symptoms occurred following treatment with piperacillin sulbactam sodium and moxifloxacin hydrochloride. A comprehensive literature review, utilizing the PubMed database, was conducted to assess case reports over the last decade where P. micra was identified as the causative agent.The literature analysis underscores the predilection of P. micra for immunocompromised populations afflicted by cardiovascular diseases, diabetes, orthopedic conditions, and tumors. Risk factors, including oral and periodontal hygiene, smoking, and alcohol consumption, were found to be associated with P. micra infections. Clinical manifestations encompassed fever, cough, sputum production, and back pain, potentially leading to severe outcomes such as Spondylodiscitis, septic arthritis, lung abscess, bacteremia, sepsis, and mortality. While conventional bacterial culture remains the primary diagnostic tool, emerging technologies like mNGS offer alternative considerations. In terms of treatment modalities, β-lactam antibiotics and nitroimidazoles predominated, exhibiting recovery rates of 56.10% (46/82) and 23.17% (19/82), respectively. This case report and literature review collectively aim to enhance awareness among clinicians and laboratory medicine professionals regarding the intricacies of P. micra-associated infections.